Language Attitudes and L2 Motivation of Korean Language Learners in Malaysia - Larisa Nikitina; Fumitaka Furuoka; Nurliana Kamaruddin (National Research University Higher School of Economics, 2020)
This study examined relationships between language attitudes and L2 motivation of learners of Korean as a Foreign Language (KFL) in a large public university in Malaysia. It employed the socio-educational model of L2 motivation and focused on the relationship between the language learners' attitudes toward speakers of the target language and their motivation to learn Korean. A systematic statistical analysis was performed to analyse the data collected from 19 (N=19) students. A robust statistical procedure adopted in this study allowed some worthwhile insights into the language attitudes-L2 motivation nexus. The findings indicated that there existed a statistically significant relationship between the language learners' instrumental orientation and their attitudes toward the speakers of Korean language.